STRATEGI PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN KAPASITAS KELEMBAGAAN KAMPUNG ADAT DI KABUPATEN SIAK PROVINSI RIAU - Amin, Raja Muhammad; ', Isril; Febrina, Rury (Universitas Riau, 2016)
This paper will examine the strategies to empower the Kampung Adat community throughthe development of institutional capacity in The Regency of Siak. The Regency of Siak is one ofthe districts that have established Desa Adat territory. Based on the Siak District RegulationNo.02/2015 specifies eight Kampung Adat located in the district of Siak. Regulation for KampungAdat setting in Siak district has gone through a long process started from; First, the opportuni-ties of formation the Kampung Adat after the issuance of Law No. 6 2014 about the village.Secondly, the formation of team to determine and the establishment of Kampung Adat. Thirdare socializing, inventarization, identification and assessment as well as recommendations fromthe Regent. Fourth is the release of regulation of Kampung Adat in Siak district, Fifth is gettingthe Registration Number from the Provinces and Sixth is getting Kampung Adat RegistrationCode from Ministry of Internal Affair. But there is a hiatus periode on the process of determina-tion of Kampung Adat in Siak district due to several things, such as yet issuance of KampungAdat Code from the Ministry of Internal Affairs, the lack of regulation related provincial levelStructuring the Kampung Adat, and the lack decree as technical guidelines for the process ofreviving traditional village. Siak district government through BPMPD address this hiatus con-ditions with suggestion to the administration of the Kampung Adat and Adat leaders in particu-lar to immediately arranged a draft form of village institutions or Adat regulations until provin-cial regulations and codes of Kampung Adat officialy released. This strategy is to accelerate theprogress of forming the institution of Kampung Adat and to avoid longer hiatus on establish-ment.Strategy of community empowerment through the development of institutional capacity bothgovernment institutions, community organizations and traditional institutions have been pre-pared by the Government of Siak, it can be seen from the activities that are directed to thestrengthening of the institutional capacity of government Kampung such as: capacity buildingfor the selected Penghulu, The chairman LPMK and Chairman BAPEKAM for periode 2015-2021, Bimtek government, kasi PMD districts and porters for all Siak Region, as well as coach-ing the village headman, the head of customary, traditional institutions chairman and chiefBAPEKAM for all Siak Region. But then again BPMPD is not yet specifically arrange the activi-ties to directly relate to the Kampung Adat because of the code for Kampung Adat is not yetobtained. At the level of Village Institution has also drawn up a planning document for develop-ment and have incorporated programs related to community development and empowerment,but still using the previous nomenclature which is Village.